The Effect of Special Exercises With Tools to Help Develop the Performance of Some Basic Skills For Players Futsal - Jabbar, Alaa; Abbas, Bassem (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The aim of the study was to prepare special exercises with auxiliary tools to develop the performance of some basic skills for futsal players and to know the effect of special exercises using auxiliary tools in developing the performance of some basic skills for futsal players. The researchers used the experimental method, which is one of the most widely used methods in the sports field because it is based on direct and realistic dealing with different phenomena and is based on observation and experimentation of its types through comparison between the group or between groups. Therefore, the researchers used the single-group design with the pre- and post-tests, which is the most appropriate for this study. The researchers defined the study community as the players of the University of Diyala futsal team, so the sample became (12) A player from a total of (18) players, representing a percentage of the sample (66.66%) of the study population for the year 2023-2024 AD, and after completing the main experiment, the researchers used the statistical package (SPSS) to process the data obtained and the researchers reached the most important conclusions that employing exercises with assistive tools had a positive impact in developing the performance of some basic skills for futsal players (scoring And scrolling) of the study, which was positively reflected on the performance of the student players of the skills under study. The prepared exercises also had an impact on developing the scoring skills. And scrolling, Researchers also recommend the use of tools and aids in developing all basic skills for all age groups.